Estimating the age of fire in the Cape flora of South Africa from an orchid phylogeny - Bytebier, Benny (The Royal Society, 2011)
Fire may have been a crucial component in the evolution of the Cape flora of South Africa, a region characterized by outstanding levels of species richness and endemism. However, there is, to date, no critical assessment of the age of the modern fire regime in this biome. Here, we exploit the presence of two obligate post-fire flowering clades in the orchid genus Disa, in conjunction with a robust, well-sampled and dated molecular phylogeny, to estimate the age by which fire must have been present. Our results indicate that summer drought (winter rainfall), the fire regime and the fynbos vegetation are several million years older than currently suggested. Summer drought and the fynbos vegetation are estimated to date back to at least the Early Miocene (ca 19.5 Ma). The current fire regime may have been established during a period of global cooling that followed the mid-Miocene Climatic Optimum (ca 15 Ma), which led to the expansion of open habitats and increased aridification. The first appearance of Disa species in the grassland biome, as well as in the subalpine habitat, is in striking agreement with reliable geological and palaeontological evidence of the age of these ecosystems, thus corroborating the efficacy of our methods. These results change our understanding of the historical mechanisms underlying botanical evolution in southern Africa, and confirm the potential of using molecular phylogenies to date events for which other information is lacking or inconclusive.